Cryobiopsy of the Pleura: An Improved Diagnostic Tool. Issue 1 (January 2018) - Tousheed, Syed Z.; Manjunath, Poojaramuddanahally Hanumantharayappa; Chandrasekar, Sagar; Murali Mohan, Bangalore Venkatraman; Kumar, Hemanth; Hibare, Kedar R.; Ramanjaneya, Ranganatha
Abstract : Background: Medical thoracoscopy (rigid and semirigid pleuroscopy) has revolutionized the approach to the diagnosis of pleural disease by offering a very high diagnostic yield. Rigid pleuroscopy offers the advantages of therapeutic intervention and larger biopsy specimens, whereas semirigid pleuroscopy using a standard biopsy forceps yields smaller and more superficial pleural samples. Cryobiopsy through semirigid pleuroscope in anecdotal studies has been used to overcome these disadvantages. We compared the safety and efficacy of cryobiopsy with conventional forceps biopsy in terms of the specimen size and diagnostic yield. Methods: We analyzed data of 139 (87 cryobiopsies and 52 forceps biopsies) patients with undiagnosed pleural effusion who underwent pleuroscopy using a semirigid pleuroscope. A cryoprobe (ERBE, 2.4 mm) was passed through the working channel of the semirigid pleuroscope, the target area of parietal pleura was frozen for an average freezing time of 8 seconds, then the semirigid pleuroscope along with the probe was forcibly withdrawn en bloc avulsing the frozen parietal pleura. Two to 3 samples were taken from each patient. Results: The diagnostic yield was 99% with cryobiopsy and 96% with forceps biopsy. The average specimen size through cryoprobe (13.2±6.7; range, 7 to 35 mm) was significantly larger than with the conventional forceps (6.8±3.3; range, 2 to 15 mm) ( P <0.001), and no major complications were noted. Conclusion: Cryobiopsy of the parietal pleura through the semirigid pleuroscope is a safe procedure with a very high diagnostic yield.